The message box / Kamaruzzaman Mohd. Sharif - Mohd. Sharif, Kamaruzzaman (1989)
This project Message Box, can be regarded as being similar to a protable cassette player whereby sound can be recorded and replayed. However, they are not directly equivalent. As example the Message Box has no rewind time so recording can be played at the press of a button. The Message Box is powered from the mains and optional battery backup facility is provided for the memory so that recorded information will not be lost when the mains is disconnected.